Reactions in a multilayered Si (substrate)/Ta/Mg/Fe/Ta/Pd thin-film structure during annealing and deuterium absorption. (15th May 2015) - Danaie, Mohsen; Fritzsche, Helmut; Peter Kalisvaart, W.; Tan, XueHai; Mitlin, David; Botton, Gianluigi A.; Huot, Jacques
Abstract: Nanolayered composites based on Fe and Mg serve as insightful model systems for understanding a wide range of hydrogen storage materials. We examined the stability of the multilayered thin-film structure Si (substrate)/Ta/Mg/Fe/Ta/Pd after deuterium absorption and desorption and after annealing the specimen at 250 °C. We employed two complementary techniques for analysis: neutron reflectometry and analytical transmission electron microscopy. The neutron reflectometry provides evidence that interdiffusion is significant at 250 °C, but with the film general structure still in place. In contrast, after deuterium absorption and desorption at the same temperature, the changes of the film structure are more severe, such that the Mg/Fe/Ta/Pd layers appear to be fully intermixed, with only the bottom Ta layer remaining intact. Electron microscopy observations indicate that annealing at 250 °C has caused a phase transformation to form Mg5 Pd2 at the upper sections of the Mg layer, with the general periodicity of the sample still maintained, in accordance with the reflectometry measurements. In the desorbed state, the layers show substantial variations in local thicknesses, with thicker regions containing a range of Mg–Pd compounds and the thinner portions remaining primarily Mg. This degradation sequence occurs despite the Fe layer remaining chemically unchanged. We provide a mechanistic description regarding the observed evolution of the multilayered structure during annealing and deuterium cycling.